Optimasi Server untuk Virtual Hosting dengan Load Balancing di PT. Kinema Systrans Multimedia - Wilhelmus Ervando Walangare; Andik Yulianto (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2025)
The rapid development of digital services demands high availability and performance from server infrastructure, especially in virtual hosting environments. The main problem faced is performance degradation and potential service failure due to surges in und-distributed traffic. This community service activity aims to implement a server optimization solution through the application of load balancing using Nginx. The method used is an IPTEKS simulation and substitution in a virtual environment that replicates real-world conditions, where a vulnerable single server is replaced by a distributed cluster. The implementation process includes setting up backend servers on the Red Hat Enterprise Linux (RHEL) operating system, security configurations, and deploying Nginx as a load balancer with the round-robin algorithm. Functional testing results show that the system successfully distributes requests evenly across all backend servers, validating the solution's effectiveness in mitigating single points of failure and enhancing scalability. Recommendations for future activities include exploring dynamic algorithms, implementing SSL/TLS security, and integrating with real-time monitoring systems.